Diversidade taxonômica em comunidades de Braconidae (Hymenoptera) em áreas de mata mesófila semidecidual do Estado de São Paulo, Brasil - Marigo, Thaís Coimbra (Universidade Federal de São Carlos, 2023)
Brazil has a megadiversity that is still poorly known, particularly regarding wasps of the Braconidae (Hymenoptera) family. Even at a regional level, there is a scarcity of studies presenting inventories of genera or species, although such information is essential for a wise management of biodiversity. In this scenario, the present study aimed to identify Braconidae at the genus level through two approaches: molecular characterization (COI gene) and morphological characterization. For this purpose, Malaise traps were used during the first half of September 2021 in contiguous areas of semideciduous mesophytic forest, reforestation, silvopastoral system, and gallery forest, located in the municipality of São Carlos, São Paulo State. A total of 339 individuals was collected, and through morphological characterization, 47 genera were identified, distributed among 19 subfamilies. Additionally, the following characteristic measurements were calculated for the Braconidae community in the studied localities: dominance, abundance, and frequency indices, as well as the richness, diversity, and evenness of the collected genera. Molecular characterization enabled the identification of 49 specimens distributed in seven genera, five of which belonged to the subfamily Microgastrinae. Although both identification strategies have the same purpose and can be used together, it is concluded that the application of one or the other may be more convenient given the presented context. Subfamilies and genera better represented in COI reference sequence libraries tend to have a higher success rate in molecular identification, while other groups can be more easily identified by morphological characters. As a contribution to future research involving Braconidae diversity, new COI sequences were deposited in an international reference library (BOLD Systems) and a new species for Brazil was described.
Taxonomic diversity in Braconidae (Hymenoptera) communities in semideciduous mesophyll forest areas of São Paulo State, Brazil
Keywords: Vespas parasitoides; Taxonomia molecular; DNA mitocondrial; Parasitoid wasps; Molecular taxonomy; Mitochondrial DNA; CIENCIAS BIOLOGICAS::ZOOLOGIA